Coordination of protrusion dynamics within and between collectively migrating border cells by myosin II - Mishra, Abhinava K. (Mol Biol Cell, 2019)
Collective cell migration is emerging as a major driver of embryonic development, organogenesis, tissue homeostasis, and tumor dissemination. In contrast to individually migrating cells, collectively migrating cells maintain cell–cell adhesions and coordinate direction-sensing as they move. While nonmuscle myosin II has been studied extensively in the context of cells migrating individually in vitro, its roles in cells migrating collectively in three-dimensional, native environments are not fully understood. Here we use genetics, Airyscan microscopy, live imaging, optogenetics, and Förster resonance energy transfer to probe the localization, dynamics, and functions of myosin II in migrating border cells of the Drosophila ovary. We find that myosin accumulates transiently at the base of protrusions, where it functions to retract them. E-cadherin and myosin colocalize at border cell-border cell contacts and cooperate to transmit directional information. A phosphomimetic form of myosin is sufficient to convert border cells to a round morphology and blebbing migration mode. Together these studies demonstrate that distinct and dynamic pools of myosin II regulate protrusion dynamics within and between collectively migrating cells and suggest a new model for the role of protrusions in collective direction sensing in vivo.